The role of telepresence as the basis of impulsive buying on e-commerce platforms - Pratiwi, Hasna Widya; Azizah, Nurifa Laksmitasari (Jurnal Mantik, 2025)
Telepresence is a concept currently popular among marketers and buyers in the current era. However, it is also possible that telepresence has shortcomings, including technical limitations, limited content, and content that is deemed inappropriate. Another problem arises from consumers, for example, many consumers still cannot interpret the concept of telepresence. This study aims to analyze the relationship between variables consisting of telepresence, shopping orientation, trust, enjoyment, and impulsive buying. This study meets the criteria of causality-based explanatory research. The sampling technique for this study was taken incidentally, totaling 200 respondents. This study uses primary data directly from respondents who answered a questionnaire via Google Form. Statistical testing of this study will be conducted using smart-PLS. The results of this study indicate a positive and significant relationship between telepresence and shopping orientation, trust, and enjoyment. Furthermore, there is a positive and significant relationship between trust and impulsive buying, while shopping orientation and trust have a positive but insignificant relationship to impulsive buying. This study encourages e-commerce platforms to innovate further in telepresence use. Future research should compare impulsive buying across platforms, as user responses and engagement may vary.